Peran matematika dalam membangun peradaban Islam - Yulianti, Silviyatus (Maliki Interdisciplinary Journal, 2023)
Mathematics plays a crucial role in developing critical thinking in individuals and shaping human life as a whole. It is essential to foster interest and a positive attitude towards mathematics to motivate learning. Through a historical perspective, mathematics offers profound insights into its long origins and its current form, revealing the essence, hypotheses, and terminologies that have evolved over time. Mathematics is recognized as the foundation of all sciences and their branches, serving as the basis for systematic knowledge in various fields. Despite some views that attempt to separate mathematics from religion, in Islam, the study of mathematics is considered a means to draw closer to Allah SWT. Mathematics learning guides individuals towards a better life, both as students and mathematicians, encompassing spiritual, theoretical, and practical dimensions. The aim of this article is to understand the position of mathematics in the perspective of Islam, the significance of mathematics in the development of Islamic civilization, and the outcomes of mathematics’ role in advancing Islamic civilization.